(untitled) (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2026)
Low physics learning outcomes among high school students, particularly on topics requiring abstract reasoning, are attributed to learning media that do not align with student characteristics and insufficient development of computational thinking and information literacy skills. The objective of this research is to develop an interactive physics learning medium based on the iSTEM model, integrated with the local culture of Lisung-Halu, using the Scratch application on the topic of Work and Energy. This medium is specifically designed to enhance students’ computational thinking and information literacy skills. The research method used is Research and Development (R&D) utilizing the 4D model. Data was collected using validation questionnaire sheets administered to five peer validators, who are prospective physics teachers. The data analysis technique involved calculating the average validation scores. The validation indicators measured included content validity, construct validity, media/display aspects, pedagogical aspects, and language suitability and readability. The results of the expert validation indicate that the developed learning medium is highly feasible for use. This study recommends the media for wider dissemination and implementation, as well as large-scale testing to analyze its effectiveness in the classroom.